Kinetics and Mechanism of Ru(III) Catalyzed Oxidation of Cyclopentanol and Cyclohexanol by Chloramine-T in Perchloric Acid Medium - Mishra, S.P.; Singh, Anju; Verma, Jyoti; Srivastava, V.K.; Singh, R.A. (Asian Journal of Chemistry, 2016)
The kinetics of Ru(III) chloride catalysed oxidation of cyclopentanol and cyclohexanol by acidic solution of chloramine-T (CAT) has been investigated. The result indicates first order kinetics with respect to each of CAT, cycloalcohols, Ru(III) and (H+). Negligible effect of [Cl–] and ionic strength variations on reaction rate was observed. Insignificant effect of addition of p-toluene sulphonamide, a reduction product of CAT, was observed. A suitable mechanism consistent with kinetic results has been proposed.